Gestión de tesorería y su contribución a la creación de valor en la empresa Becatel Perú S.A.C, Trujillo, 2019 - Espinola Ibañez, Viviana Liseth (2020)
The main objective of this research is to determine the relationship of Treasury Management and its contribution to the creation of value of the company Becatel Perú S.A.C, Trujillo, year 2019, thus seeking to maximize profits. This research is descriptive and not experimental, because it obtained information directly, without modifying or altering the data, likewise the population is the company Becatel Peru SAC, and as a sample certain workers in the areas. For the development of this research Surveys were used to analyze the economic and financial information. It is concluded that the company in 2019, improved its treasury management, which had a favorable impact on the creation of value, this was evidenced after the analysis of financial indicators of both liquidity, management, solvency - profitability, as well as the EVA, which increased by 68.56%, in addition, it was demonstrated through Pearson's correlation, the existence of a close direct positive relationship between treasury management and value creation. It is recommended to apply the treasury management design in order to anticipate the cash needs and surpluses for a correct financial decision.